ASSESSING MACROECONOMIC POLICIES IN CAMBODIA: A SIMPLE MODEL FOR POLICY ANALYSIS - M, Plödt; C. A, Reicher (Economics and Statistics Research Journal (ESRJ), 2022)
To support macroeconomic decision-making in developing countries with low-frequency data and without a tradition of model-based policy analysis, we propose a simple macro-fiscal model that focuses on both monetary and fiscal policies. The model is designed to simulate and forecast macroeconomic policies, particularly for scenario analysis, and to show the potential impact of Covid-19. The model takes into account key characteristics of the Cambodian economy and is calibrated using a manageable range of variables. Despite its limitations, the model generates policy scenarios with past empirical analyses of the Cambodian economy. The results, alongside expert judgment, can guide policy advice and inform policymakers about medium-term transmissions channels. The model's parsimony makes it useful in countries without sophisticated models to support macroeconomic decision-making